Isolation and identification of bacteriocidal lactobacillus in a locally fermented meat sausage - Lualhati, Maria Gracia A.; Benedicto, Ana Maria Q. (2001., 2001)
Lactic acid bacteria were isolated and characterized from locally fermented sausage, longanisa. These were plated on total plate count agar, glucose yeast peptone agar, acidified potato dextrose agar and lactobacillus medium. MRS agar. Lactobacilli colonies were grouped according to their characteristic culture growth in plates and were further purified. Majority of the growths of the lactobacillus isolates were characteristic of the specified genera. Gram staining gave positive results to ten out of the eleven isolates. The isolate with the largest zone of inhibition in Disc Agar Assay was selected and was further characterized. The antibacterial agent discovered was microaerophilic or facultative anaerobic, acidophilic, mesophilic and can tolerate concentrations of salt up to 10%. Colony growth displayed opaque optical features, no pigmentation and highly turbid broth growths that are characteristic for the genera of lactobacillus. Biochemical tests showed negative liquefication of gelatin, absence of starch hydrolysis, and negative result for indole test. Positive result in catalase test was attributed to depleted glucose during growth. Acid was formed from galactose, fructose and glucose. Possible identities given were L. plantarum anf L. brevis. Mechanism for antibacterial activity was not investigated, however, it is suggested that it may be hydrogen peroxide formation, lactic acid production and bacteriocin activity. Both possible identities have a history of bacteriocin production.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Sausage -- Microbiology; Meat -- Preservation